The Impact of Social Media Usage on MSME Performance: The Role of Innovation Capability as a Moderating Factor - Sahetapy, Willyan; Biay, Agustinus; Rusdi, Rusdi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The study seeks to investigate the impact of social media use on Micro, Small and Medium Enterprise (MSME) performance, and the moderating effect of innovation capability on the link. Amid the digital technology boom, MSMEs leverage TikTok, Instagram, Facebook among others to widen market reach, brand presence and talk to their audience directly. The opportunity and threat of social media but but can be a double edged sword in terms of the mSME’s level of capability to innovate in relation to marketing strategy. Innovation capability (product development, technology use, market responsiveness) as a moderator has proved to have the most mediating processes between social media and MSMEs performance. This research is quantitative by distributing a questionnaire of 300 MSME respondents that using social media. The findings indicate that the utilisation of social media has a significant effect on the performance of MSMEs, which is also moderated by innovativeness. Its effect on perfornlance is however not the same For all SNSs. This finding indicates that innovative-related MSMEs have potential to utilize social media to improve business performance and growth better.